Kuntowijoyo Prophetic Social Science And Its Relevance To Material Religion - Maulana, Abdullah Muslich Rizal; Sufratman, Sufratman; Aliah, Ainun (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2023)
This research aimed to comprehend Kuntowijoyo’s idea of Prophetic Social Science (Ilmu Sosial Profetik) from Material Religion perspective. Because it is intricately related to a matrix or network of components such as people, divine beings or forces, institutions, artifacts, places, and communities, it is interesting to come to a more profound comprehension of Islam in the sense of Kuntowijoyo’s Prophetic Social Science; enriching its understanding in a deeper and broader context of materiality. Carried out as literature research, this paper utilized the content analysis method to select and unify Kuntowijoyo’s works and then explained the results gained from the analysis. This research concluded that Prophetic Social Science was capable to be implemented within the framework of Material Religion; reconstructing an advanced conception of science, culture, and community from the Islamic perspective.